Metabolism of IMM-H004 and Its Pharmacokinetic-Pharmacodynamic Analysis in Cerebral Ischemia/Reperfusion Injured Rats - Zhang, Ziqian; Liu, Dandan; Jiang, Jianwei; Song, Xiuyun; Zou, Xiaowen; Chu, Shifeng; Xie, Kebo; Dai, Jungui; Chen, Naihong; Sheng, Li; Li, Yan (Frontiers in Pharmacology, 2019)
IMM-H004, a derivative of coumarin, is a promising candidate for the treatment of cerebral ischemia. The pharmacodynamic mechanisms of IMM-H004 are still under exploration. The present study was conducted to explore the pharmacoactive substances of IMM-H004 from the perspective of drug metabolism. Four metabolites of IMM-H004 including demethylated metabolites M1 and M2, glucuronide conjugate IMM-H004G (M3) and sulfated conjugate M4 were found in rats in vivo. IMM-H004G was the major metabolite in rats and cultured human hepatocyte, and UDP-glucuronosyltransferase (UGTs) were found to catalyze the metabolism of IMM-H004 in human liver microsomes (HLMs) and rat liver microsomes (RLMs) with high capacity (Vmax at 3.25 and 5.04 nmol/min/mg protein). Among 13 recombinant human UGT isoforms, UGT1A7, 1A9, 1A8 and 1A1 appeared to be primarily responsible for IMM-H004G formation. The exposure and duration of IMM-H004G (28948 h×ng/mL of AUC, 6.61 h of t1/2β) was much higher than that of the parent drug (1638 h×ng/mL of AUC, 0.42 h of t1/2β) in transient middle cerebral artery occlusion/ reperfusion (MCAO/R) rats, consistent with the malondialdehyde inhibition effect for at least 10 h. Further pharmacological study revealed that IMM-H004G exhibited a similar neuroprotective activity to that of parent drug on both oxygen-glucose deprivation injured PC12 cells and transient MCAO/R injured rats. These results demonstrate that both prototype and IMM-H004G are the active pharmaceutical substances, and IMM-H004G, at least in part, contributes to the maintenance of anti-cerebral ischemia efficacy of IMM-H004.